MENINGKATKAN HASIL BELAJAR PPKN DENGAN MENGGUNAKAN METODE PEMBERIAN TUGAS SISWA KELAS V SDN 012 SILIKUAN HULU - Waldiyem (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study was the low Civics (PPKn) learning outcomes of fifth-grade students at SD Negeri 012 Silikuan Hulu. This research employed classroom action research conducted in Grade V of SD Negeri 012 Silikuan Hulu and was carried out in two cycles. The data used in this study focused on improving students’ Civics learning outcomes. The results of the study indicated an improvement in students’ Civics (PPKn) learning outcomes. This was consistent with the research findings, which showed that based on the preliminary data, the average student score was 60. In the first cycle, the average score increased to 65, and in the second cycle, it further increased to 70. In addition, the number of students who achieved mastery also increased. In the preliminary data, only 6 students met the mastery criteria; this number increased to 9 students in the first cycle and further rose to 12 students in the second cycle. Based on these findings, it can be concluded that the application of the assignment method effectively improves Civics (PPKn) learning outcomes of fifth-grade students at SD Negeri 012 Silikuan Hulu.